Cross-Accent Intelligibility of Speech in Noise: Long-Term Familiarity and Short-Term Familiarization. Issue 3 (March 2014) - Smith, Rachel; Holmes-Elliott, Sophie; Pettinato, Michèle; Knight, Rachael-Anne
Listeners must cope with a great deal of variability in the speech signal, and thus theories of speech perception must also account for variability, which comes from a number of sources, including variation between accents. It is well known that there is a processing cost when listening to speech in an accent other than one's own, but recent work has suggested that this cost is reduced when listening to a familiar accent widely represented in the media, and/or when short amounts of exposure to an accent are provided. Little is known, however, about how these factors (long-term familiarity and short-term familiarization with an accent) interact. The current study tested this interaction by playing listeners difficult-to-segment sentences in noise, before and after a familiarization period where the same sentences were heard in the clear, allowing us to manipulate short-term familiarization. Listeners were speakers of either Glasgow English or Standard Southern British English, and they listened to speech in either their own or the other accent, thereby allowing us to manipulate long-term familiarity. Results suggest that both long-term familiarity and short-term familiarization mitigate the perceptual processing costs of listening to an accent that is not one's own, but seem not to compensate for them entirely, even when the accent is widely heard in the media.